Human papilloma virus 16/18 genotypes in patients with squamous cell carcinoma of cervix in northeast Iran - Ayatollahi, Hossein (Niger Med J, 2014)
BACKGROUND: A relation has been established between infection with high-risk types of human papilloma virus (HPV) and development of cervical cancer. To estimate the risk of HPV infection for cervical malignancies, we conducted a case-control study in northeast Iran. MATERIALS AND METHODS: This study was carried out on 123 paraffin embedded blocks with exact diagnosis of squamous cell carcinoma (SCC). A total of 100 cervical tissue specimens with normal histopathology product of hysterectomy were also used as control. Both groups were tested for the presence of HPV DNA and HPV 16/18 subtypes using PCR assay. RESULTS: Large non-keratinising subtype of cervical carcinoma was the most frequent one (62.6%), followed by keratinising and small cell subtypes (27% and 10%, respectively). Overall prevalence of HPV infection in SCC of cervix was 34.2% (42 out of 123 cases). HPV 16 was the most common type in this group (21 cases, 17.1%), followed by HPV 18 (16 cases, 13%) and other subtypes (5 cases, 4.1%). In this study, overall prevalence of HPV infection in control group was 12% (including 3% HPV 16; 5% HPV 18 and 4% other subtypes). CONCLUSION: Although association of HPV 16/18 and SCC of cervix was relatively higher than control group, compared with the previous study, the association between cervical SCC and HPV infection was significantly lower in our study; and possibly, the other risk factors play a major role in carcinogenesis of cervical carcinoma in this region.